Uso do glyphosate em sistemas sombreados com forrageiras do gênero Urochloa - Victor Augustus Vasconcelos de Oliveira (2024)
The use of herbicides in integrated production systems disregards the light conditions in the tree understory. Interactions between plant x herbicide x environment can alter the response of Urochloa genotypes to glyphosate and desiccation for direct planting in straw. The objectives of the work were: 1- evaluate the response of Urochloa genotypes subjected to desiccation by glyphosate, in full sun and in an artificially shaded environment; 2- evaluate the desiccation by glyphosate of U. decumbens and U. brizantha and the straw decomposition process in a silvopastoral system (SSP) with different levels of shading. The first objective was achieved with two experiments, one in shading and the other in full sun, in a 5 x 6 factorial scheme. In the first factor, 5 forages of the genus Urochloa were used, three of which were hybrids (Cayana grass, Mulato II grass and Sabiá grass), and two species (U. brizantha and U. ruziziensis). In the second factor, doses 2160 were used; 1622.4; 1080; 524.4; 273.6 and 0.0 g a.e. ha-1 of glyphosate. With 72.55% ± 1.1% of light restriction, control of Marandu, Cayana, Mulato and Ruziziensis grasses was obtained with 273.6 g ha-¹ of glyphosate and for Sabiá grass with 524.4 g ha-1. The savings in spending on glyphosate for 100% shading control were 74.7% for Ruziziensis grass, 75.7% for Sabiá grass and 87.3% for Marandu, Mulato and Cayana grasses, compared to obtained in full sun. The second objective was achieved with two experiments, one with U. decumbens and the other with U. brizantha, in subdivided plots, with 4 cultivation strips with different distances (between 1 and 4, between 4 and 7, between 7 and 10 m and in full sun) in relation to the tree line. In the subplots, doses 1440, 1080, 720, 360 and 0.0 g a.e. ha-1 of glyphosate were allocated to control U. decumbens and 2160, 1680, 1200, 720 and 0.0 g a.e. ha-¹ of glyphosate for U. brizantha. For U. decumbens, all doses tested controlled plants in shaded environments. In full sun, control occurred with doses of 1080 and 1440 g ha-1. For U. brizantha, all environments showed 100% control with the application of doses greater than 1200 g ha-1. At 720 g ha-1, control of U. brizantha was lower in full sun and in the center of the tree lines, whereas, in full sun, control was insufficient. In SSP, with a spacing between eucalyptus rows of 20 m, U. decumbens and U. brizantha are controlled with 360 and 720 g ha-1 of glyphosate, respectively, regardless of the distance from the trees. The cost savings on glyphosate for 100% control in the SSP were 66.67% for U. decumbens and 40.0% for U. brizantha, compared to that obtained in full sun cultivation. With the application of glyphosate there is a drop in the quantum efficiency of photosystem II and in the electron transport rate, with a more pronounced response from 360 and 720 g ha-1 of glyphosate, for U. decumbens and U. brizantha, respectively, regardless of the distance in relation to the trees. The plants show greater decomposition in the central bands. The release of CO2 from the soil occurs closer to the trees.